Thermoelectric Modulation of Neat Ti3C2Tx MXenes by Finely Regulating the Stacking of Nanosheets - Tang, Junhui; Zhu, Renyang; Pai, Ya‑Hsin; Zhao, Yan; Xu, Chen; Liang, Ziqi (Nano-Micro Letters, 2024)
Emerging two-dimensional MXenes have been extensively studied in a wide range of fields thanks to their superior electrical and hydrophilic attributes as well as excellent chemical stability and mechanical flexibility. Among them, the ultrahigh electrical conductivity (σ) and tunable band structures of benchmark Ti3C2Tx MXene demonstrate its good potential as thermoelectric (TE) materials. However, both the large variation of σ reported in the literature and the intrinsically low Seebeck coefficient (S) hinder the practical applications. Herein, this study has for the first time systematically investigated the TE properties of neat Ti3C2Tx films, which are finely modulated by exploiting different dispersing solvents, controlling nanosheet sizes and constructing composites. First, deionized water is found to be superior for obtaining closely packed MXene sheets relative to other polar solvents. Second, a simultaneous increase in both S and σ is realized via elevating centrifugal speed on MXene aqueous suspensions to obtain small-sized nanosheets, thus yielding an ultrahigh power factor up to 156 μW m−1 K−2. Third, S is significantly enhanced yet accompanied by a reduction in σ when constructing MXene-based nanocomposites, the latter of which is originated from the damage to the intimate stackings of MXene nanosheets. Together, a correlation between the TE properties of neat Ti3C2Tx films and the stacking of nanosheets is elucidated, which would stimulate further exploration of MXene TEs. Highlights: 1 Investigation of dispersing solvents on processing Ti3C2Tx thin films revealed that deionized water is superior to realize tight stacking and high orientation of MXene nanosheets. 2 A simultaneous elevation of Seebeck coefficient and electrical conductivity of neat Ti3C2Tx films is achieved by increasing the centrifugal speed of MXene aqueous suspensions due to the energy filtering effect. 3 Further construction of Ti3C2Tx nanocomposites significantly strengthens Seebeck coefficient yet disrupts the stacking of MXene nanosheets.